Anhydrobiosis in yeast: cell wall mannoproteins are important for yeast Saccharomyces cerevisiae resistance to dehydration. Issue 8 (28th April 2016) - Borovikova, Diana; Teparić, Renata; Mrša, Vladimir; Rapoport, Alexander
Abstract: The state of anhydrobiosis is linked with the reversible delay of metabolism as a result of strong dehydration of cells, and is widely distributed in nature. A number of factors responsible for the maintenance of organisms' viability in these conditions have been revealed. This study was directed to understanding how changes in cell wall structure may influence the resistance of yeasts to dehydration–rehydration. Mutants lacking various cell wall mannoproteins were tested to address this issue. It was revealed that mutants lacking proteins belonging to two structurally and functionally unrelated groups (proteins non‐covalently attached to the cell wall, and Pir proteins) possessed significantly lower cell resistance to dehydration–rehydration than the mother wild‐type strain. At the same time, the absence of the GPI‐anchored cell wall protein Ccw12 unexpectedly resulted in an increase of cell resistance to this treatment; this phenomenon is explained by the compensatory synthesis of chitin. The results clearly indicate that the cell wall structure/composition relates to parameters strongly influencing yeast viability during the processes of dehydration–rehydration, and that damage to cell wall proteins during yeast desiccation can be an important factor leading to cell death. Copyright © 2016 John Wiley & Sons, Ltd.